A synthetic small molecule stalls pre-mRNA splicing by promoting an early-stage U2AF2-RNA complex. Issue 8 (19th August 2021) - Chatrikhi, Rakesh; Feeney, Callen F.; Pulvino, Mary J.; Alachouzos, Georgios; MacRae, Andrew J.; Falls, Zackary; Rai, Sumit; Brennessel, William W.; Jenkins, Jermaine L.; Walter, Matthew J.; Graubert, Timothy A.; Samudrala, Ram; et al.
Summary: Dysregulated pre-mRNA splicing is an emerging Achilles heel of cancers and myelodysplasias. To expand the currently limited portfolio of small-molecule drug leads, we screened for chemical modulators of the U2AF complex, which nucleates spliceosome assembly and is mutated in myelodysplasias. A hit compound specifically enhances RNA binding by a U2AF2 subunit. Remarkably, the compound inhibits splicing of representative substrates and stalls spliceosome assembly at the stage of U2AF function. Computational docking, together with structure-guided mutagenesis, indicates that the compound bridges the tandem U2AF2 RNA recognition motifs via hydrophobic and electrostatic moieties. Cells expressing a cancer-associated U2AF1 mutant are preferentially killed by treatment with the compound. Altogether, our results highlight the potential of trapping early spliceosome assembly as an effective pharmacological means to manipulate pre-mRNA splicing. By extension, we suggest that stabilizing assembly intermediates may offer a useful approach for small-molecule inhibition of macromolecular machines. Graphical abstract: Highlights: A small molecule binds to U2AF2 and promotes its association with splice site RNA Promoting the U2AF2-RNA complex stalls the initial stages of spliceosome assembly The small molecule exacerbates pre-mRNA splicing defects of U2AF1 mutant cells Cancer-relevant U2AF1 mutant cells are preferentially killed by the small molecule Abstract : Many cancers and myelodysplasias are associated with pre-mRNA splicing defects. Chatrikhi et al. describe a hit compound that stalls pre-mRNA splicing at the initial stages of spliceosome assembly by binding to U2AF2 and promoting U2AF2-RNA association. Treatment with the molecule alters splicing and preferentially kills cells expressing a cancer-relevant U2AF1 mutant.